TO CALCULATION OF VENTILATION FOR SHOPFLOORS AT CONDITIONS OF SEGREGATION OF A FEW NOXIOUS MATTERS - Ryzhkov, Vadim; Belokon’, Karina; Manidina, Eugenia; Troits’ka, Helen; Radchenko, Yurii (Scientific Journal "Metallurgy", 2021)
This article discusses the problem of finding the minimum necessary air exchange toremove several harmful substances from the volume of the working room with a different natureof action. The authors determined the required performance of the ventilation unit to reduce theconcentration of harmful substances to acceptable values for a given period of time. The conditionsfor the simultaneous release of several harmful substances into the air of the working zonewere considered. As a basis for analysis, the well-known main differential equation of air exchange(ventilation) was adopted. After appropriate mathematical transformations, the authorsobtained equations describing the performance of the ventilation unit for four options for the entryof harmful substances into the air. The first option involves the release of substances of multidirectionalaction (that is, each substance has an effect on the body of a certain nature, independentof the effects of other substances). For example, it can be a substance with a general toxic effect, such as mercury, chemically asphyxiating, like carbon monoxide and a substancewith fibrogenic action, like silicon dioxide. The second option is the allocation of unidirectionalsubstances with the effect of summation (additive effect). Moreover, the effects of exposure tosubstances are summarized. Such properties are, for example, hydrocarbons: methane,ethane, propane, etc. The third option is the release of unidirectional substances with an enhancingeffect, when one substance enhances the toxic effect of another (like ethanol and aniline).The fourth option is the release of unidirectional substances with a weakening effect, whenone substance weakens the toxic effect of another (like chlorine and sulfur dioxide). For eachoption, dependencies are proposed that allow you to determine the minimum required flow rateof ventilation air.